Sildenafil improves hippocampal brain injuries and restores neuronal development after neonatal hypoxia–ischemia in male rat pups - Armin Yazdani (Nature Portfolio, 2021)
Abstract The hippocampus is a fundamental structure of the brain that plays an important role in neurodevelopment and is very sensitive to hypoxia–ischemia (HI). The purpose of this study was to investigate the effects of sildenafil on neonatal hippocampal brain injuries resulting from HI, and on neuronal development in this context. HI was induced in male Long–Evans rat pups at postnatal day 10 (P10) by a left common carotid ligation followed by a 2-h exposure to 8% oxygen. Rat pups were randomized to vehicle or sildenafil given orally twice daily for 7 days starting 12 h after HI. Hematoxylin and eosin staining was performed at P30 to measure the surface of the hippocampus; immunohistochemistry was performed to stain neurons, oligodendrocytes, and glial cells in the hippocampus. Western blots of the hippocampus were performed at P12, P17, and P30 to study the expression of neuronal markers and mTOR pathway. HI caused significant hippocampal atrophy and a significant reduction of the number of mature neurons, and induced reactive astrocytosis and microgliosis in the hippocampus. HI increased apoptosis and caused significant dysregulation of the normal neuronal development program. Treatment with sildenafil preserved the gross morphology of the hippocampus, reverted the number of mature neurons to levels comparable to sham rats, significantly increased both the immature and mature oligodendrocytes, and significantly reduced the number of microglia and astrocytes. Sildenafil also decreased apoptosis and reestablished the normal progression of post-natal neuronal development. The PI3K/Akt/mTOR pathway, whose activity was decreased after HI in the hippocampus, and restored after sildenafil treatment, may be involved. Sildenafil may have both neuroprotective and neurorestorative properties in the neonatal hippocampus following HI.